Development and study of the stability of comenic acid solutions - T. A. Bitkina; A. V. Basevich (Разработка и регистрация лекарственных средств)
Introduction. The article presents the development of solutions based on the comenic acid substance. The criteria of the studied compositions that affect their stability during storage are evaluated within the framework of the Quality-by-Design concept. The optimal compositions of comenic acid solutions have been established.Aim. The purpose of the study is to develop solutions based on the comenic acid substance and determine the most stable variants of execution.Materials and methods. The study of comenic acid solutions was carried out by using a laboratory pH meter PB-11-P11 (SARTORIUS, Germany) and a liquid/ion chromatograph "Stayer" ("Akvilon" JSC, Russia).Results and discussion. The study made it possible to determine the most stable compositions of solutions based on the comenic acid substance and to establish optimal indicators of their stability criteria. It was found that solutions of comenic acid are the most stable in the pH range: from 4.0 to 6.0. At the same time, regardless of the studied methods of neutralization of comenic acid, solutions are unstable at concentrations of 25 mg/ml or more.Conclusion. As a result of the study, the optimal compositions of solutions based on the comenic acid substance were determined. A comparative analysis of excipients that increase the solubility of comenic acid in aqueous solvents is performed. The stability criteria of the studied solutions are established and their values for ensuring the stability of the developed drug are determined.